FINANCIAL LITERACY ON THE USE OF SHARIA BANKING PRODUCTS THROUGH FINANCIAL INCLUSION AMONG PURWAKARTA REGENCY - Ilyas Ilyas; Eti Jumiati; Cece Cece (Journal Tourism Nomic, 2026)
This study aims to analyze the effect of financial literacy on the use of Islamic banking products through financial inclusion as a mediating variable in Purwakarta Regency. A quantitative approach was employed using a survey method, with data collected from 148 respondents selected through simple random sampling. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that financial literacy has a significant positive effect on the use of Islamic banking products, although the magnitude of the effect is relatively small. Financial literacy also significantly influences financial inclusion. Furthermore, financial inclusion has a strong and significant effect on the use of Islamic banking products. Mediation testing indicates that financial inclusion plays a significant role as an intervening variable in the relationship between financial literacy and the use of Islamic banking products. These findings suggest that improving financial literacy can enhance financial inclusion, which in turn increases the utilization of Islamic banking products. Therefore, strengthening financial education and expanding access to financial services are essential strategies to promote the growth of Islamic banking in regional areas such as Purwakarta.